2022
DOI: 10.1186/s13018-022-03168-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcomes of minimally invasive total hip arthroplasty: a systematic review

Abstract: Introduction The present systematic review investigated possible factors which may influence the surgical outcome of minimally invasive surgery for total hip arthroplasty (MIS THA). Methods In January 2022, the Embase, Google Scholar, PubMed, and Scopus databases were accessed. All the clinical trials investigating the clinical outcome of MIS THA were considered. Results Data from 9486 procedures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 140 publications
0
16
0
Order By: Relevance
“…A 2022 systematic review of 9486 THAs investigated possible factors that may influence the surgical outcome of minimally invasive THA. It found that older age and higher BMI may be negative prognostic factors for minimally invasive THA and that the clinical outcome is strongly influenced by patients' preoperative status 43 . A 2019 retrospective study of 116 patients found that return to work after hip and knee arthroplasty was not significantly influenced by the type of surgery or the physical demands of the job.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2022 systematic review of 9486 THAs investigated possible factors that may influence the surgical outcome of minimally invasive THA. It found that older age and higher BMI may be negative prognostic factors for minimally invasive THA and that the clinical outcome is strongly influenced by patients' preoperative status 43 . A 2019 retrospective study of 116 patients found that return to work after hip and knee arthroplasty was not significantly influenced by the type of surgery or the physical demands of the job.…”
Section: Discussionmentioning
confidence: 99%
“…It found that older age and higher BMI may be negative prognostic factors for minimally invasive THA and that the clinical outcome is strongly influenced by patients' preoperative status. 43 A 2019 retrospective study of 116 patients found that return to work after hip and knee arthroplasty was not significantly influenced by the type of surgery or the physical demands of the job. Patients returned to work between 5.9 and 7.7 weeks after hip/knee replacement.…”
Section: Discussionmentioning
confidence: 99%
“…By observing the results reported, most studies reported a shorter length of hospital stay for SP, so we supposed that the analysis result was plausible and the effect of publication bias was small. There existed a strong publication bias in the outcomes of the time to start activity postoperatively and incision length, both of which could be influenced by differences in bone cement, differences in hip implants, and differences in the patient's underlying diseases, age, gender, and BMI to some extent [ 67 ]. For example, women had longer incision lengths than men; heavier patients had longer incision lengths than those with less weight; patients with more underlying diseases required a longer time to get out of bed.…”
Section: Discussionmentioning
confidence: 99%
“…Another 19 were excluded because they focused on preoperative treatment or postintervention efficacy or effectiveness [13][14][15][16][17][18][19][20], did not report results about postoperative chronic pain [21][22][23][24][25], had no systematic review [26], overlooked preoperative risk factors [7], or investigated different surgical approaches [27][28][29][30]. Finally, a total of 18 reviews [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] were included in the umbrella (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%